The communist manifesto - Marx, Karl, 1818-1883.; Engels, Friedrich, 1820-1895.; Findlay, L. M. (Peterborough, Ont. : Broadview Press, 2004)
"L. M. Findlay's elegant new translation is a work of textual and historical scholarship. Few books have had as much of an impact on modern history as The Communist Manifesto. Since it was first published in 1848, it has become the rallying cry for revolutionary movements around the world. This new Broadview edition draws on the 1888 Samuel Moore translation supervised by Engels - the standard English version in Marxist discourse - and on the original Helen Macfarlane translation into English of 1850." "Throughout, Findlay draws on a variety of disciplines and maintains a broadranging perspective. Among the appendices are Engels' "Draft of a Communist Confession of Faith," correspondence and journalism of Marx and Engels, ten illustrations, and eight additional influential political manifestos from the eighteenth and nineteenth centuries."--BOOK JACKET.
Marx and Engels : a brief chronology -- The Communist Manifesto -- App. A. From Flora Tristan's Tour de France, September 1844 -- App. B. Letter from Engels to Marx, November-December 1846 -- App. C. Engels, draft of a communist confession of faith, 9 June 1847 -- App. D. Marx, "the communism of the Rheinischer Beobachter," September 1847 -- App. E. Communist Journal, No. 1, September 1847 -- App. F. Engels, "principles of communism," late October 1847 -- App. G. Letter from Engels to Marx, 23-24 November 1847 -- App. H. Engels, "on the history of the communist league," 1885 -- App. I. Engels, "the labour movement in America." : preface to the American edition of The condition of the working class in England, 26 January 1887 -- App. J. Engels, "notes on my journey through America and Canada," late September 1888 -- App. K. Engels, "impressions of a journey round America," late September 1888 -- App. L. Manifestoes.
Translation of: Manifest der Kommunistischen Partei.
Includes bibliographical references (p. 252-254).
Keywords: Communism